Turnover Intention Satuan Pengaman: Ketidakpastian Kerja, Kepercayaan Pada Pimpinan, dan Moderasi Kinerja Individu - Fajar Fathur Rahman; Eny Rochaida; Doddy Adhimursandi (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the influence of job insecurity and trust in leadership on resignation intentions among security personnel at PT. Garuda Kencana Abadi Balikpapan, with individual performance as a moderating variable. The background of the study is based on the phenomenon of high turnover among security personnel, which indicates instability in work relationships and perceptions of leadership. The research method used a quantitative approach with Partial Least Squares Structural Equation Modeling analysis techniques. Data were obtained from questionnaires distributed to security personnel, with the number of respondents meeting the research criteria. The results showed that job insecurity had a positive and significant effect on resignation intentions, meaning that the higher the feeling of job insecurity, the greater the worker's desire to leave. Conversely, trust in leadership had a significant negative effect on resignation intentions, meaning that the higher the trust in leadership, the lower the worker's tendency to quit. Furthermore, individual performance was shown to moderate the relationship between the two independent variables on resignation intentions, although the strength differed across paths. These findings strengthen the theory of job insecurity and trust in leadership and provide practical implications for company management in creating a stable work environment, improving leadership quality, and strengthening individual performance to reduce employee resignation rates.;. Keywords: Leadership_Trust; Job_Uncertainty; Performance; Turnover_Intention; Trust